Coffee and gastrointestinal health: a review - Wan Kamarul Zaman, Wan Syamimi; Loh, Su Peng; Mohd Esa, Norhaizan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Coffee is a well-known beverage being processed from coffee beans of either Arabica and/or Robusta. Observational and experimental research on coffee shows positive health impact. Coffee often relates with dyspeptic condition (i.e. Gastric release) and manifest Gastro-esophageal Reflux (GERD) and peptic ulcer (PU) diseases. Despite much contradictive results, epidemiological studies were inclined towards debunking the possible relationship between coffee and gastrointestinal diseases. Putative compounds were experimentally found to be chlorogenic acid (CQA), caffeine (CAFF), βN-alkanoyl-5-hydroxytryptamide (C5HT), N-methylpyridinium (NMP), chlorogenic acid lactones (CQL) and hydroxybenzenes in coffee that leads to gastric release. The type 2 bitter taste receptors (TAS2Rs), were physiologically involve in the gastric acid secretion. These contrarily results need much considerations involving genetic, types of coffee used and the compounds in coffee that might interact causing gastrointestinal problem.